2020
DOI: 10.1007/s41810-020-00077-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 Pandemic Lockdown on Air Quality Using Satellite Imagery with Ground Station Monitoring Data in Most Polluted City Kolkata, India

Abstract: Immediate lockdown (March 24-May 31, 2020) of industrial activity and traffic flows has been announced by the government of India across the country after the declaration of World Health Organization that the Novel Coronavirus (SARS-CoV-2) outbreak is pandemic. In this study, we tried to estimate the air quality improvement during the pre-lockdown period (January 1-March 23, 2020) by comparing the lockdown period (March 24-May 31, 2020). From the results, we found the highest reduction in the concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This reduction is mainly influenced by the combined effect from the higher mixing layer, low anthropogenic activities (Sarkar et al., 2021 ) and disintegration of PM 10 into smaller particles (Gogikar et al., 2018 ). The NS, PL and PT sampling phase exhibited the concentration level range of 82.17‐546.21 μgm −3 , 82.15‐272.06 μgm −3 and 60.61‐186.77 μgm −3 , respectively, where the concentration levels during NS and PT were found to be mainly contributed from clusters of small industries (Kabiraj & Gavli, 2020 ), tanneries (Sarkar et al., 2021 ), thermal power plant (Biswas & Ayantika, 2021 ) and vehicular emissions (Banerji & Mitra, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reduction is mainly influenced by the combined effect from the higher mixing layer, low anthropogenic activities (Sarkar et al., 2021 ) and disintegration of PM 10 into smaller particles (Gogikar et al., 2018 ). The NS, PL and PT sampling phase exhibited the concentration level range of 82.17‐546.21 μgm −3 , 82.15‐272.06 μgm −3 and 60.61‐186.77 μgm −3 , respectively, where the concentration levels during NS and PT were found to be mainly contributed from clusters of small industries (Kabiraj & Gavli, 2020 ), tanneries (Sarkar et al., 2021 ), thermal power plant (Biswas & Ayantika, 2021 ) and vehicular emissions (Banerji & Mitra, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The aerosol sampling was carried out in the University of Calcutta's Taraknath Palit Siksha Prangan campus (22.526 N 88.363 E) as illustrated in Exhibit 1 , which is situated in Ballygunge, an urban locality in the central part of Kolkata. The sampling site is surrounded by clusters of small‐scale industrial units mainly comprised of tanneries and metal processing units as described by Kabiraj and Gavli ( 2020 ) in their study. They also mentioned the major pollutant contributors as traffic, industrial units and power plants, which was further elaborated in a study by Sarkar et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on the effect of total lockdown due to COVID-19 pandemic on air quality across the globe have been reported, indicating various degrees of decline in the air pollution levels in their respective study areas. In India, effects of controlled emission on the quality of atmospheric air during the pandemic era was investigated and improved air quality was reported with reduced pollution levels ranging from 10% to 53.61% (Sharma et al, 2020;Kabiraj and Gavli, 2020;Singh, 2021a). Study by Ambade et al (2021) showed that COVID-19 lockdowns significantly reduced the concentrations of Black carbon, PAHs and PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, according to (Son et al 2020 ) the lower level of air pollution made indirect health benefits to the public health. However, it has had a positive impact on the environment, specifically on air quality, as a result of partial to total lockdown in various countries around the world (Kabiraj and Gavli 2020 ). The level of air pollution remarkably decreased during different lockdown phases in India (The Central Pollution Control Board, 2020).…”
Section: Introductionmentioning
confidence: 99%